Urinary Incontinence Among Older Adults Living In The Rural Area Of A Municipality In Southern Brazil - Alessandra Coelho Dziekaniak; Rodrigo Dalke Meucci; Juraci Almeida Cesar (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To measure the prevalence of and identify factors associated with the occurrence of urinary incontinence (UI) in older adults (aged 60 years or older) living in the rural area of the municipality of Rio Grande, southern Brazil. METHOD: In a single-visit approach, interviewers systematically visited 80% of the households in the rural area of this municipality between April and October 2017. A standardized questionnaire was administered to older adults for information on demographic characteristics, socioeconomic characteristics, lifestyle habits, and morbidity pattern. Prevalence ratio (PR) was used as the effect measure. The c2 test was used to compare proportions. Poisson regression models with robust variance were used in the multivariate analysis. RESULTS: Of 1028 respondents (90.9% of the total), 15.9% (95%CI 13.6-18.1) reported having UI. Adjusted analysis showed that the risk of UI increases with age and is 3 times hig her in women (PR = 3.72; 95%CI 2.66-5.21). Perception of health status as fair, poor, or very poor had a PR = 1.68 (95%CI 1.25-2.26) and having 2 or more comorbidities had a PR = 1.73 (95%CI 1.17-2.55). CONCLUSION: In this study, the prevalence of UI was 15.9%, being significantly more prevalent in women, in older adults aged 65 years or older, in those with 2 or more morbidities, and in those perceiving their health status as fair, poor, or very poor.